From learners to creators: Empowering English education through AI-generated digital storytelling - Pipit Novita (Universitas Muhammadiyah Malang, 2026)
The integration of artificial intelligence (AI) has transformed education by offering new possibilities for personalised, creative, and technology-enhanced learning. In English language education, AI opens opportunities to reimagine learning approaches and materials, enabling more diverse, interactive, and student-centred experiences. While AI integration often focuses on supporting learning tasks, less attention has been paid to empowering students as creators of learning materials. This paper reports a qualitative study exploring university students’ experiences of creating English storybooks enhanced with AI-generated illustrations for primary learners. Forty-five pre-service teachers created original narratives, embedded moral values, adapted language for young readers, and designed visuals using AI tools, supported by teacher feedback. The completed storybooks were then presented in real classroom settings. Data from structured reflection reports were analysed using thematic analysis. The findings reveal hybrid creativity through human–AI collaboration and pedagogical agency, as participants critically evaluated and adapted AI outputs to meet pedagogical goals and learner needs. These findings challenge views of AI as merely an efficiency tool, demonstrating that, within a carefully designed pedagogical project, AI can support a shift in pre-service teachers’ roles from learners to creators through human-led decision-making. The study highlights the importance of student-led content creation supported by AI and guided by ethical and pedagogical responsibility, with human judgment remaining central in English language education.